2006
DOI: 10.1016/j.nuclphysa.2005.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of ϕ mesons in γA reactions

Abstract: We present a theoretical analysis of inclusive photoproduction of φ mesons in nuclei. In particular the dependence of the total φ meson yield on the target mass number is investigated. The calculations are done using the semi-classical BUU transport approach that combines the initial state interaction of the incoming photon with the coupled-channel dynamics of the final state particles. The conditions of the calculations are chosen such as to match the set-up of a recent experiment performed at SPring8/Osaka. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
43
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 36 publications
5
43
0
1
Order By: Relevance
“…A momentum-dependent increase of the φ in-medium broadening, as suggested by Wood et al [11], and shown for the collisional part of the broadening by Mühlich et al [9], might partly explain the different results, but this has certainly not been unambiguously proven so far. The high statistics of 7000-10000 φ per target provided by the existing ANKE data allows us to search for such a possible variation in the momentum range of 0.6 GeV/c < p φ < 1.6 GeV/c, and an investigation of this is in progress.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…A momentum-dependent increase of the φ in-medium broadening, as suggested by Wood et al [11], and shown for the collisional part of the broadening by Mühlich et al [9], might partly explain the different results, but this has certainly not been unambiguously proven so far. The high statistics of 7000-10000 φ per target provided by the existing ANKE data allows us to search for such a possible variation in the momentum range of 0.6 GeV/c < p φ < 1.6 GeV/c, and an investigation of this is in progress.…”
mentioning
confidence: 89%
“…From this they deduced an increase in the width by a factor 3.6 at normal nuclear density [7]. A much larger in-medium broadening was reported by SPring-8 [8] (compare also [9,10]) and the very recent JLab [11] measurements. Both these experiments studied the variation of the φ production cross section with the atomic number A.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…With this method we have first analysed both results on the experimental determination of the nuclear transparency ratio for φ mesons [7], measured by a Japanese group at SPRING8 that lead to an unexpectedly large in-elastic cross section for φN interactions. We have found that indeed cross sections about a factor 3 larger than those theoretically expected are needed to explain the mentioned data, in line with a simple Glauber analysis by the SPRING8 group.…”
Section: Analysis Of Cbelsa/taps ω Photoproduction Datamentioning
confidence: 99%
“…The ϕ production in nuclei has been intensively studied both experimentally [1][2][3][4], as well as in theoretical analyses [4][5][6][7][8]. The ϕ nuclear transparency ratio, measured in proton-induced and photoproduction experiments, points to a large absorption in nuclei, consistent with widths about one order of magnitude larger than the one from its dominant decay toKK in vacuum.…”
Section: Introductionmentioning
confidence: 99%